Job Crafting and Resilience among Medical Interns: The Moderating Role of Social Media Use Intensity. - Yang, Dan; Cao, Zhe; Sampaio, Francisco (Perspectives in Psychiatric Care, 2024)
COVID‐19 brought many difficulties for medical workers' mental health. They tend to exhibit a high turnover rate, which has deteriorated the situation of high demands on the healthcare workforce. Thus, enhancing medical interns' resilience is of great significance. Previous studies have delved into how job crafting relates to resilience, but there has been limited exploration of how the three dimensions of job crafting interplay with resilience. Thus, our research examined the moderating role of social media use intensity in associations between task crafting, cognitive crafting, relational crafting, and resilience. A total of 605 medical interns were obtained. The results revealed that task crafting, cognitive crafting, and relational crafting exhibited significant and positive associations with resilience. More importantly, social media use intensity moderated associations between task crafting, cognitive crafting, and resilience, with these associations being weaker for individuals with high levels of social media use intensity. However, the moderating role of social media use intensity was not significant between relational crafting and resilience. Finally, the findings provided some guidance for instructors to enhance medical interns' resilience and thus prepare them for employment.